Membangun Pemahaman Karakter Kejujuran Melalui Permainan Tradisional Anak Usia Dini Kelompok B di Taman Kanak-Kanak Sawitto Kabupaten Pinrang - Fitri, Riskal (Edumaspul: Jurnal Pendidikan, 2022)
This reserch aims tofind out the efforts of trachers in building childrens understanding, espciallu honesty characters through traditional games and knowing dende’ games in building understanding of childrens honesty characters in Sawitton kindergarten Pinrang. This research is a descriptive qualitative method that aims to describe objectively. The subcets of research are children aged 5-6 yeats in Sawitto kindergarten Pinrang. It’s consists of 10 childrens. This research uses data collection techniques through observations made tochildren and teachers, interviews with teachers, and documentation. The results of the reserch are based on the observation that the character childrens honesty in traditional game actions, especially dende’ games, includes all indicators (obeying rules or activites while playing. Behavehonesty. Helpers, polite, respecetful, sportsmanlike, etc.Understand several commands simultaneously, understand the rules in game, and take responsibility and admit mistake) are well executed. Achievement of the development of hoenst attitude of children develops very well.